Characterization of AL2O3 Nano Particles in Engine Oil for Enhancing the Heat transfer rate - Sridhar Yesaswi, Ch; Ajay Krishna, K; Pavan Gopal Varma, A; Girish, K; Jagadeesh Varma, K (International Journal of Engineering and Technology, 2018)
Selection of suitable engine oils becoming more challenging for automobile engineers. Life of the engine majorly depends upon engine oil, type of fuel being used and various other thermal and structural characteristics of the engine. Dissipation of heat is one of the major consideration in the design of automobile engines. Generally engine oils are used for the lubrication between piston and cylinder but to enhance the cooling effectiveness Nano-particles are added in the lubricant, so that internal heat generation in the engines can be minimized. Nano-fluids are playing a vital role in heat transfer applications because of its enhanced thermal conductivity nature and generally these fluids are colloidal mixture of Nano particles and base fluids. Intense research studies over Nano fluids are very high because of their sublime behavior.Recently. Advanced research over Nano technology has gone to a situation where two or more Nano particles are made to mix in a base fluids and generally we call this as hybrid Nano fluids. In this work, preparation of Al2O3 nanoparticles and mixing them with 10W30 engine oil were carried out. By various techniques thermal characteristics of fluid are identified with different parameters.Â Â